‘Continentes’ or ‘conjugati’? An analysis about the Augustine’s sexual dispositive in the context of the Jovinianist Controversy - Veloso, Wendell dos Reis (Romanitas - Revista de Estudos Grecolatinos, 2018)
This article analyzes the thinking of Augustine, Bishop of Hippo in Northern Roman Africa, on sexualities in two treatises written in the beginning of the fifth century in the context of the Jovinianist Controversy: De Bono Coniugali and De Sancta Virginitate. With the help of the theoretical reflections of Michel Foucault it is pointed out that the bishop’s discursive attempt to harmonize marriage with the praise of virginity has led him to adopt an ambivalent position, so that his position can be understood as in part anti-reproductive and, objectively, anti-sexuality active. As a result, the reproductive sexuality granted indulgently is linked to the long historical process of naturalization of what we now call heteronormativity.